2005
DOI: 10.1007/bf02702007
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of physico-chemical characteristics of the Haldia channel of Hooghly estuary, India

Abstract: seasons have been studied. Salinity varied spatially and temporally and seasonally during ebb and flood tide conditions. Water temperature showed a difference of 10 • C in winter to summer. Temperature did not vary much vertically as it is a well-mixed estuary. Strong currents exceeding 100 cm s −1 were observed during peak ebb and flood tide conditions irrespective of the season. Longitudinal eddy diffusion coefficient (K x) was estimated as 757 m s −1 and 811 m 2 s −1 during summer and post-monsoon seasons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 6 publications
1
36
0
Order By: Relevance
“…Thus, the presence of H 2 S in the pore water is not necessarily an indication of the prevalence of anoxic condition in the overlying water column. The observation that dissolved O 2 concentrations in the surface water of the estuary are not very different than those in the bottom water (Sadhuram et al, 2005) provides support to the contention that anoxic conditions do not prevail in the water column of the estuary. Ghosh et al (2013) also cite the occurrence of CH 4 reported by Biswas et al (2007), and contend that oxidation of this methane could be a source of the lower d 13 C DIC values observed in their study.…”
Section: Degradation Of Organic Carbon and Biological Respirationmentioning
confidence: 56%
See 3 more Smart Citations
“…Thus, the presence of H 2 S in the pore water is not necessarily an indication of the prevalence of anoxic condition in the overlying water column. The observation that dissolved O 2 concentrations in the surface water of the estuary are not very different than those in the bottom water (Sadhuram et al, 2005) provides support to the contention that anoxic conditions do not prevail in the water column of the estuary. Ghosh et al (2013) also cite the occurrence of CH 4 reported by Biswas et al (2007), and contend that oxidation of this methane could be a source of the lower d 13 C DIC values observed in their study.…”
Section: Degradation Of Organic Carbon and Biological Respirationmentioning
confidence: 56%
“…2) to $8 m (25 ft) at the mouth of the estuary (CIFRI, 2012). The Hooghly main channel is much deeper than its distributary, the Muriganga channel ($6 m; Sadhuram et al, 2005).The width of the river at the mouth of the estuary is $25 km (Mukhopadhyay et al, 2006). Annual rainfall over the last 5 years (2009)(2010)(2011)(2012)(2013) in and around the Hooghly River estuary varied from $1310 mm to $2300 mm (IMD, 2013).…”
Section: The Study Areamentioning
confidence: 98%
See 2 more Smart Citations
“…The depth of the water column varies from 10 to 15 m (Mukhopadhyay et al 2006). Hooghly is a well-mixed estuary because of shallow depth (average 6 m) and intense tidal mixing (Sadhuram et al 2005). The estuary gets semidiurnal tides with a maximum range of 5.5 m at spring and minimum 1.8 m at neap.…”
Section: Study Areamentioning
confidence: 99%